Phases of Faith; Or, Passages from the History of My Creed - Newman, Francis William, 1805-1897 (Salt Lake City, UT : Project Gutenberg, 2004)
"Phases of Faith; Or, Passages from the History of My Creed" by Francis William Newman is a reflective narrative written in the late 19th century. This work delves into the author's personal journey of faith and theological questioning, traversing his early religious beliefs through to later struggles with established doctrines. It presents a profound exploration of belief, faith, and the tensions between personal conviction and communal adherence to religious dogma. At the start of this volume, Newman introduces himself as a man in the process of reconciling his youthful creed with the complexities of his evolving understanding of faith. He recounts his early years of piety, his formative encounters with mentors, and the eventual disillusionment he experiences with traditional doctrines such as Election, Infant Baptism, and Episcopacy. The opening chapters detail his intellectual and spiritual conflicts, as he grapples with the seeming contradictions in ecclesiastical teachings and strives for a more authentic, personal faith that aligns with his convictions about the essence of Christianity. This narrative sets the stage for a deeper exploration into the subsequent stages of his creed development, illustrating a rich tapestry of spiritual inquiry and insight. (This is an automatically generated summary.)
Release date is 2004-04-01
Produced by PG Distributed Proofreaders
Keywords: Christianity; Newman, Francis William, 1805-1897; Unitarians -- Biography; Faith; Spiritual biography